2016
DOI: 10.1093/rb/rbw031
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic osteogenesis and angiogenesis regulated by porous architecture of hydroxyapatite scaffolds with similar interconnecting structure in vivo

Abstract: The macro-pore sizes of porous scaffold play a key role for regulating ectopic osteogenesis and angiogenesis but many researches ignored the influence of interconnection between macro-pores with different sizes. In order to accurately reveal the relationship between ectopic osteogenesis and macro-pore sizes in dorsal muscle and abdominal cavities of dogs, hydroxyapatite (HA) scaffolds with three different macro-pore sizes of 500–650, 750–900 and 1100–1250 µm were prepared via sugar spheres-leaching process, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 65 publications
1
34
0
Order By: Relevance
“…Indeed, during preclinical in vivo studies, grafts with optimized physicochemical properties have presented better outcomes than those with suboptimal properties. For instance, calcium phosphate phase composition, macro‐porosity (ie, macro‐pore size and interconnectivity) and bioactivity have been directly related to the in vivo tissue response, neovascularization and bone‐forming potential in ectopic and orthotopic sites . Moreover, presence of a submicron surface topography and micro‐porosity has been linked to substantially enhanced bone‐inducing properties of calcium phosphates …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, during preclinical in vivo studies, grafts with optimized physicochemical properties have presented better outcomes than those with suboptimal properties. For instance, calcium phosphate phase composition, macro‐porosity (ie, macro‐pore size and interconnectivity) and bioactivity have been directly related to the in vivo tissue response, neovascularization and bone‐forming potential in ectopic and orthotopic sites . Moreover, presence of a submicron surface topography and micro‐porosity has been linked to substantially enhanced bone‐inducing properties of calcium phosphates …”
Section: Discussionmentioning
confidence: 99%
“…For instance, calcium phosphate phase composition, [38][39][40][41][42][43] macroporosity [44][45][46][47][48][49][50] (ie, macro-pore size and interconnectivity) and bioactivity 51 have been directly related to the in vivo tissue response, neovascularization and bone-forming potential in ectopic and orthotopic sites. [40][41][42][43] Moreover, presence of a submicron surface topography and micro-porosity has been linked to substantially enhanced boneinducing properties of calcium phosphates.…”
Section: Discussionmentioning
confidence: 99%
“…According to the studies performed by Karageorgiou and Kaplan, scaffolds with pore sizes >300 μm are recommended for repairing large bone defect as they resulted in enhanced new bone and capillary formations. Among various types of scaffolds, excellent osteoinductions have been shown in the ones with pore sizes within the range of 500‐1200 μm . It was also demonstrated that ceramic scaffold with 300‐500 μm pores is optimal for osteogenesis; the ones with 300 μm pores, which exhibited inferior bone ingrowth .…”
Section: Introductionmentioning
confidence: 97%
“…Among various types of scaffolds, excellent osteoinductions have been shown in the ones with pore sizes within the range of 500-1200 μm. 5,6 It was also demonstrated that ceramic scaffold with 300-500 μm pores is optimal for osteogenesis; the ones with 300 μm pores, which exhibited inferior bone ingrowth. 7 Regarding vascularization for the optimal pore size, Chang et al 8 reported that large pores in β-tricalcium phosphate scaffold were beneficial for the blood vessel ingrowth, and the pores smaller than 400 μm limit the growth of blood vessels.…”
mentioning
confidence: 99%
“…It is generally accepted that the pore geometry in a scaffold, including pore size, pore shape, porosity, and pore interconnecting pattern, plays an important role in cell adhesion, proliferation, and migration as well as tissue ingrowth [38,39]. Lager pore sizes favor tissue ingrowth and vascularization, resulting in better osteogenesis, while smaller pores lead to osteochondral ossification [40]. An ideal bone scaffold should have 100-600 µm pore size with 60-80% porosity to provide enough space for cell migration, tissue ingrowth, and vascularization.…”
Section: Discussionmentioning
confidence: 99%